International perspectives on democratization and peace - Ganesan, Narayanan (Bingley, U.K. : Emerald Publishing Limited, 2020)
Since at least the 1990s, international mediation efforts have investigated whether civil conflicts could be resolved through democratization. The results have been mixed, and within the scholarship there is no real framework for how to approach the question, let alone any agreement on the answers. Drawing on concrete cases from three continents, and bringing together contributions from political scientists, historians, area specialists, and international relations experts, International Perspectives on Democratization and Peace takes stock of all the efforts expended in pursuit of peaceful, democratic settlements to civil conflict and provides a sorely needed framework for thinking clearly about the role of democratization in international mediation processes. In three sections, authors give a philosophical and historical elaboration of the key questions, investigate seven applied case studies that survey the impact of democratization on civil conflicts in diverse global contexts, and discuss how US preference for its own interests over international democratization has delayed, but not indefinitely forestalled, the process of democratization in many parts of the globe, a process that demands continued, serious analysis and discussion. This book is a must-read not for scholars within international relations, international political economy, development studies, political science, and peace and conflict studies.
Chapter 1. Open Roads to Peace and Democratization; Mónica Dias -- Chapter 2. Post-Nuclear / Post-Colonial Challenges to Democratization in the Pacific; Robert Jacobs -- Chapter 3. Democratization, Peace and the Differences betyween Asian and Western Approaches: The Case of Cambodia; Makiko Takemoto -- Chapter 4. Democratization and its impact on ethnic conflict and peace in Myanmar; Narayanan Ganesan -- Chapter 5. The peace process in Sri Lanka: The challenges for democracy after decades of civil conflict and terrorism; Raquel Duque -- Chapter 6. A democratic tradition as the background to armed conflict: The paradox of the Colombian case; Margarita Cuervo -- Chapter 7. The roads to reinvigorate the peace agreements: Between electorial and justice reforms in Guatemala; Jose Carlos Sanabria -- Chapter 8. The Angolan Process of Peace and Democratization: a case study; Raul Tati -- Chapter 9. Peace and conflict in Mozambique: A long Road to democracy; António L Fontes Ramos -- Chapter 10. Comparative Analysis of the Regional Security System of Europe and Asia: dilemmas of the Asian Security System; Gen Kikkawa -- Conclusion. Impact of democratization on civil conflict; Narayanan Ganesan.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Democratization; Political Science -- Political Ideologies / Democracy; Political structures: democracy